Advances on Self-Regulation Models: A New Research Agenda Through the SR vs ER Behavior Theory in Different Psychology Contexts - de la Fuente, Jesús; Martínez-Vicente, José Manuel; Santos, Flavia H.; Sander, Paul; Fadda, Salvatore; Karagiannopoulou, Evangelia; Boruchovitch, Evely; Kauffman, Douglas F. (Frontiers in Psychology, 2022)
The aim of this paper is to demonstrate how Bandura’s Social Cognitive Theory (1986) influenced the development of several complementary models of the construct of Self-Regulation. Building on the foundation of Self-Determination Theory, SDT (2000), and Zimmerman’s Self-Regulation Theory, SR (2001), with their assumptions, contributions, goddesses, and limitations, we come to the Self- vs External Regulatory Theory, SR-ER (2021). Finally, we integrate recent evidence demonstrating the explanatory adequacy of the SR vs ER model for different psychological constructions in different settings related to education, health, clinical practice and social work. Finally, a new theoretical and empirical research agenda is presented, to continue testing the adequacy of SR vs ER assumptions, and to better understand the behavioral variability of the different constructs studied.